Clinico-epidemiological profile of chronic otitis media at a tertiary care hospital - Kishore, Hubballi Ravi; R., Reshma P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media equates with the term chronic suppurative otitis media that is no longer advocated as it is not necessarily a result of the gathering of pus. Incidence of this disease is higher in developing countries especially among lower socioeconomic society because of malnutrition, overcrowding, poor hygiene, inadequate health care facility and recurrent upper respiratory tract infection. Methods: Eighty patients with chronic otitis media were included. After obtaining written and informed consent, they were subjected to detailed history taking and examination. Various risk factors of chronic otitis media and the morbidity caused by the disease were studied. Data was analyzed using IBM SPSS version 22. Results: The most common age group was 21-30 years with male predominance. Central perforation was the most common type of perforation. Various factors like low socioeconomic status, rural setup, overcrowding, malnutrition, indoor cooking, recurrent acute otitis media, recurrent upper respiratory tract infection, naso-respiratory allergies, habit of swimming, taking bath in pond, ear probing were found to cause the onset of the disease and worsen of the disease process. Conclusions: Chronic otitis media results in various morbidity including increased financial burden, restricts daily activities, hence affects the psychological mindset and lowers the confidence of the patient giving them a feeling of social outcast. A proper awareness must be spread regarding these factors, maintaining personal hygiene, improving nutrition and immunity. An immediate consultation with the otorhinolaryngologist will reduce the disease progression and hence the complications.